(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2013)
Variation in the in-vitro antioxidant properties and α-amylase inhibitory activity of Tetrapleura tetraptera pod was assessed at two phenologic stages of the fruit development, that is, the mature green (MG) and ripe brown (RB) stages. RB pod (RBP) had significantly higher (P < 0.05) antioxidant phenolic phytochemicals - total phenol, tannin and total flavonoid - levels than the MG pod (MGP). Conversely, MGP had significantly higher (P < 0.05) total carotenoid and vitamin C contents than RBP. Methanolic extracts of both MGP and RBP had appreciable trolox equivalent antioxidant capacity (TEAC), and were effective in reducing Fe3+ to Fe2+. However, RBP extract had significantly higher (P < 0.05) TEAC and ferric reducing antioxidant power (FRAP) than MGP extract. Furthermore, both MGP and RBP extracts scavenged 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical in a dose-dependent manner, with the half maximal inhibitory concentration (IC50) of RBP (0.11 mg/ml) being lower than that of MGP (0.16 mg/ml). Both extracts also displayed potent inhibitory activity against porcine pancreatic α-amylase in a dose-dependent manner, having IC50 values of 0.33 mg/ml and 0.46 mg/ml for RBP and MGP respectively. Therefore, T. tetraptera pod is more potent in scavenging free radicals and inhibiting pancreatic α-amylase in vitro when fully ripe than when green, and thus could be more effective in alleviating oxidative stress and managing postprandial hyperglycemia in type 2 diabetes at the fully ripe stage than at the mature green stage.